2009
DOI: 10.1002/cbf.1544
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Ca2+‐ATPase activity in the homogenate, plasma membrane and microsomes of the salivary glands of streptozotocin‐induced diabetic rats

Abstract: Diabetes has been implicated in the dryness of the mouth, loss of taste sensation, sialosis, and other disorders of the oral cavity, by impairment of the salivary glands. The aim of the present study was to examine the plasma membrane, microsomal, and homogenate Ca(2+)-ATPase activity in the rat submandibular and parotid salivary glands of streptozotocin-induced diabetes. We have also examined the influence of the acidosis state on this parameter. Diabetes was induced by an intraperitoneal injection of strepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
0
5
1
4
Order By: Relevance
“…Abnormal Ca 2þ signaling in the salivary glands leads to dryness of the mouth, loss of taste sensation, sialosis, and other disorders of the oral cavity (Nicolau et al 2009 ). Inhibition of this release with dantrolene reduces cell injury (Wei and Perry 1996).…”
Section: Salivary Glandsmentioning
confidence: 99%
“…Abnormal Ca 2þ signaling in the salivary glands leads to dryness of the mouth, loss of taste sensation, sialosis, and other disorders of the oral cavity (Nicolau et al 2009 ). Inhibition of this release with dantrolene reduces cell injury (Wei and Perry 1996).…”
Section: Salivary Glandsmentioning
confidence: 99%
“…Numerous studies have reported the effects of experimental diabetes induced either by STZ or aloxan on the structure and functions of salivary glands of animals,7, 28, 29 including the antioxidant parameters status in various tissues 4, 7, 28. Studies based on aloxan‐diabetes rats showed significant decrease in DNA, RNA and amylase content in rat PA glands, increase in the peroxidase activity,7, 8, 30 increase of SGTL1 (responsible for the reabsorption of water in the duct cells) protein expression in ductal cells in diabetic rats,31 increase in the extracellular matrix proteins in PA,18 decrease in Ca‐ATPase, unbalance of Ca in the salivary gland32 and finally, an increase in the glycation of calmodulin 33. Despite all studies, the mechanism of the damages caused by diabetes is still not clear.…”
Section: Discussionmentioning
confidence: 99%
“…For example, basolateral membrane vesicles isolated from syncytiotrophoblast of insulin-dependent diabetic patients display increased PMCA activity (359), while reduced PMCA activity or expression has been identified in parotid and submandibular salivary glands, kidney, and brain synaptosomes of streptozotocin-induced diabetic rats (260,347,421).…”
Section: Camentioning
confidence: 99%